Strategy To Improve Consistency Of Planning And Budgeting In The Public Works And Spatial Planning Department Of Palembang City - Marvita Debora Ginting; Anna Fariyanti; Andrea Emma Pravitasari (SEAN Institute, 2024)
The Palembang City PUPR Office as one of the priority regional apparatuses in Palembang City, receives the second largest percentage of budget every year after education affairs. Therefore, consistency in budget planning is important to be implemented so that the allocation of the budget can produce optimal development performance. Consistency in budget planning needs to be prioritized because this is the main indicator in assessing local government performance. This ensures that all government programs and activities are implemented effectively in order to achieve predetermined goals. Analyze, describe the influencing factors, formulate strategies to improve consistency in planning and budgeting, at the Palembang City Public Works and Spatial Planning Office. The data collection method used in this study was by conducting observations, structured interviews and questionnaires by expert respondents. The determination of respondents was carried out using the purposive sampling technique. The data analysis method used descriptive analysis using the Planning and Budgeting Consolidation Matrix (MKPP). The conclusion of this study is that the planning and budgeting process at the Palembang City Public Works and Spatial Planning Service still experiences inconsistencies in activities and budget deviations, factors that influence the consistency of planning and budgeting are the components of HR competency in planning and budgeting, alternative strategies in efforts to improve the consistency of planning and budgeting (1) improving the quality and quantity of planning apparatus owned through coordination and cooperation between the Regional Government and the Central Government together with institutions/universities. (2) optimizing the target of regional apparatus development through aligning central government policies towards planning and budgeting, (3) increasing the capacity of regional apparatus leaders in dealing with the uncertainty of transfer funds and local revenues, and (4) aligning and consistent regional apparatus planning and budgeting in accordance with the RPJMD and RPJMN.